(untitled) (Research, Society and Development, 2021)
SARS-Cov-2 has altered social behavior worldwide, causing drastic changes in the population’s routine, its impacts have still been gradually perceived and several questions have arisen in the face of the pandemic, the possibility of interspecies transmission casts doubt on the participation of domestic animals in the epidemiology of the disease. The present study demonstrates the detection of the SARS-CoV-2 through RT-qPCR technique in unvaccinated domestic cats with free access outside the house, domiciled in Alta Floresta city (State of Mato Grosso, Brazil) with report of clinical respiratory manifestations and its possible transmission among individuals of the same species. Information like this is valuable and contributes to the understanding of the epidemiological chain of COVID-19 and may eventually assist in the establishment of future protocols for control and eradication programs, however the presence of positive animals needs to be carefully analysed and studied among specialists in order to avoid negative impacts on their relationship, owner and their pets, aiming to prevent unnecessary abandonment and sacrifices.